Parametrical Synthesis of Radio Devices with the Set Quantity of Identical Cascades for Inclusion Variants of Jet Two-port Networks between a Nonlinear Part and Loading - A. A. Golovkov; A. V. Fomin (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The ability to analytically determine some parameters of various radio devices, which are optimal according to the criterion of providing the set values of the modules and phases of transfer functions at the required number of frequencies, significantly reduces the time for numerical optimization of the rest of the parameters according to the criterion of forming the required frequency response and frequency response in the frequency band. Until now, such problems with respect to radio devices have been solved only for one stage of the "nonlinear part – matching device" or "matching device – nonlinear part" type. As a matching device, reactive, resistive, complex, or mixed quad-poles were used.Aim. Development of algorithms for parametric synthesis of radio devices with an arbitrary number of identical cascades of the "nonlinear part – matching reactive quadrupole" type according to the criterion of ensuring the specified frequency characteristics. Non-linear parts are represented as a non-linear element and parallel or serial current or voltage feedback.Materials and methods. Four-pole theory, matrix algebra, decomposition method, method of synthesis of microwave control devices, numerical optimization methods.Results. Systems of algebraic equations are formed and solved. Models of optimal quadrupole conductors are obtained in the form of mathematical expressions for determining the relationships between the elements of their classical transmission matrix and for finding the frequency dependences of the resistances of two-pole conductors.Conclusion. It is shown that the frequency characteristics of the studied radio devices from the same stages are identical or similar to the frequency characteristics of radio devices from the same stage, but with the signal source and load resistances changed in a certain way. Such schemes are called equivalent. A comparative analysis of the theoretical results (frequency response and frequency response of radio devices) obtained by mathematical modeling in the "MathCad" system, and the experimental results obtained by circuit modeling in the "OrCAD" and "MicroCap" systems, shows their satisfactory agreement.